ThE DIFFUSION OF THE TAX CULTURE AND ITS INFLUENCE IN ThE PERUVIAN EDUCATIONAL SYSTEM - Gómez Gallardo, Luz Marina Marina (2014)
This article intends to inform that in recent years, research in the tributary field has made a significant progress; the tax culture must be based on values that tend to the common good, and in the educational system it seeks to raise awareness in teachers and students of the practice of these values; for that, the school must make a commitment to train citizens able to define, defend and enforce standards of living in Peru; as well as create a country in which every Peruvian feels and knows that it is possible to fulfill personal and social aspirations. This conviction leads us to combine our efforts towards the formation of the children and future critical and participatory citizens, responsible, creative, tolerant and transparent in their actions, so that they will try to make possible a real and profound transformation of the society in which they live.